MicroRNA-218 instructs proper assembly of hippocampal networks - Taylor, Seth R; Kobayashi, Mariko; Vilella, Antonietta; Tiwari, Durgesh; Zolboot, Norjin; Du, Jessica X; Spencer, Kathryn R; Hartzell, Andrea; Girgiss, Carol; Abaci, Yusuf T; Shao, Yufeng; De Sanctis, Claudia; et al. (eLife, 2023)
The assembly of the mammalian brain is orchestrated by temporally coordinated waves of gene expression. Post-transcriptional regulation by microRNAs (miRNAs) is a key aspect of this program. Indeed, deletion of neuron-enriched miRNAs induces strong developmental phenotypes, and miRNA levels are altered in patients with neurodevelopmental disorders. However, the mechanisms used by miRNAs to instruct brain development remain largely unexplored. Here, we identified miR-218 as a critical regulator of hippocampal assembly. MiR-218 is highly expressed in the hippocampus and enriched in both excitatory principal neurons (PNs) and GABAergic inhibitory interneurons (INs). Early life inhibition of miR-218 results in an adult brain with a predisposition to seizures. Changes in gene expression in the absence of miR-218 suggest that network assembly is impaired. Indeed, we find that miR-218 inhibition results in the disruption of early depolarizing GABAergic signaling, structural defects in dendritic spines, and altered intrinsic membrane excitability. Conditional knockout of Mir218-2 in INs, but not PNs, is sufficient to recapitulate long-term instability. Finally, de-repressing Kif21b and Syt13, two miR-218 targets, phenocopies the effects on early synchronous network activity induced by miR-218 inhibition. Taken together, the data suggest that miR-218 orchestrates formative events in PNs and INs to produce stable networks.
Keywords: microRNA; development; network stability; GABAergic interneurons; miR-218